Anomalous Dynamics of Magnetic Anisotropic Colloids Studied by XPCS. Issue 46 (13th August 2018) - Pal, Antara; Zinn, Thomas; Kamal, Mohammad Arif; Narayanan, Theyencheri; Schurtenberger, Peter
Abstract: The influence of an applied magnetic field on the collective dynamics of novel anisotropic colloidal particles whose shape resembles peanuts is reported. Being made up of hematite cores and silica shells, these micrometer‐sized particles align in a direction perpendicular to the applied external magnetic field, and assemble into chains along the field direction. The anisotropic dynamics of these particles is investigated using multispeckle ultrasmall‐angle X‐ray photon correlation spectroscopy (USA‐XPCS). The results indicate that along the direction of the magnetic field, the particle dynamics strongly depends on the length scale probed. Here, the relaxation of the intermediate scattering function follows a compressed exponential behavior at large distances, while it appears diffusive at distances comparable or smaller than the particle size. Perpendicular to the applied field (and along the direction of gravity), the experimental data can be quantitatively reproduced by a combination of an advective term originating from sedimentation and a purely diffusive one that describes the thermal diffusion of the assembled chains and individual particles. Abstract : Measuring anisotropic collective dynamics of magnetic particles in a magnetic field : Ultrasmall‐angle X‐ray photon correlation spectroscopy is used to investigate the length‐scale‐dependent collective dynamics of peanut‐shaped magnetic particles that self‐assemble into chains.